Lanterne rouge : the last man in the Tour de France - Leonard, Max (New York : Pegasus Books, 2015)
Shares the lesser-known stories of last-place finishers in the Tour de France, recounting the inspirational and occasionally absurd events that shaped their efforts.
Issoire -- The first last man -- The survivor -- The yellow jersey -- The rebel -- The debutant -- The escape artist -- The domestique -- The showman -- The maverick -- The fall guy -- The sprinter -- The brothers -- Saint-Flour -- Lanternes rouges, from 1903 to 2013.
Includes bibliographical references (pages 253-254) and index.
Keywords: Cycling -- History; SPORTS & RECREATION -- Cycling; Cycling; 20151031 NEW LIST; Anecdotes; History; Anecdotes; History